PENGARUH KOMPETENSI SDM DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI PADA LINGKUP BADAN RISET DAN INOVASI DAERAH KABUPATEN KUTAI TIMUR - Fanny Novita Sari; Aji Ratna Kusuma; Nanok Fitriyadi; Fatma Eka Sari (Program Studi Manajemen, 2025)
This study aims to analyze the influence of human resource (HR) competence and workload on employee performance through organizational commitment as a mediating variable at the Regional Research and Innovation Agency (BRIDA) of East Kutai Regency. The research employs a quantitative method with an explanatory research approach. The population consists of all Civil Servants (ASN) at BRIDA East Kutai, totaling 45 individuals, using a saturated sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results indicate that HR competence and workload have a positive and significant effect on both organizational commitment and employee performance directly. However, organizational commitment does not have a significant effect on employee performance and is unable to mediate the relationship between HR competence and workload on performance. In conclusion, technical competence and a proportional workload are the main pillars driving employee performance at BRIDA East Kutai. Meanwhile, the emotional aspect in the form of organizational commitment has not shown a significant impact on performance, possibly because it remains normative or merely reflects a sense of obligation. Therefore, strengthening HR capacity through technical training and improving a transparent workload distribution system should become strategic priorities for the organization.